2023
DOI: 10.1101/2023.03.01.530249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptional buffering and 3ʹUTR lengthening are shaped during human neurodevelopment by shifts in mRNA stability and microRNA load

Abstract: The contribution of mRNA half-life is commonly overlooked when examining changes in mRNA abundance during development. mRNA levels of some genes are regulated by transcription rate only, but others may be regulated by mRNA half-life only shifts. Furthermore, transcriptional buffering is predicted when changes in transcription rates have compensating shifts in mRNA half-life resulting in no change to steady-state levels. Likewise, transcriptional boosting should result when changes in transcription rate are acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…The longer 3'UTRs, the more cis-regulatory elements residing and more stable gene expression [38][39][40] . We found that the high-redundant targets have the longest 3'UTRs (peaking at 1,024 ~ 2,048 bp), followed by the low-redundant (peaking at 256 ~ 512 bp), non-redundant (peaking at 128 ~ 256 bp) and non-motif targets (peaking at 128 ~ 256 bp; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The longer 3'UTRs, the more cis-regulatory elements residing and more stable gene expression [38][39][40] . We found that the high-redundant targets have the longest 3'UTRs (peaking at 1,024 ~ 2,048 bp), followed by the low-redundant (peaking at 256 ~ 512 bp), non-redundant (peaking at 128 ~ 256 bp) and non-motif targets (peaking at 128 ~ 256 bp; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The rates of RNA synthesis and degradation can be kinetically coupled by establishing a feedback loop between RNA synthesis in the nucleus to degradation of their corresponding RNAs in the cytoplasm ( 62 69 ). This mechanism has been well established in yeast and recently demonstrated in human cells ( 70 , 71 ); however, all the studies were done in a steady-state condition and its regulatory mechanisms, particularly under a dynamic condition, remain elusive (reviewed in ref. 63 ).…”
Section: Discussionmentioning
confidence: 99%